2002
DOI: 10.1016/s0308-521x(02)00026-4
|View full text |Cite
|
Sign up to set email alerts
|

Changing systems for supporting farmers' decisions: problems, paradigms, and prospects

Abstract: All correct reasoning is a grand system of tautologies, but only God can make direct use of that fact. The rest of us must painstakingly and fallibly tease out the consequences of our assumptions. (Herbert Simon in 'The Sciences of the Artificial', p.15)Decision support systems (DSS), like other information systems (IS) before them, were designed to serve functions deemed by 'management scientists' to be potentially useful to managers. But the unwelcome fact is that the use of agricultural DSSs by managers of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
187
0
7

Year Published

2010
2010
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 326 publications
(195 citation statements)
references
References 34 publications
1
187
0
7
Order By: Relevance
“…Another challenge is to build models that will easily be appropriable by farmers and that will allow them to consider in-depth changes. Building them in a participatory way with farmers could be one way of making them more appropriable (Newman et al, 2000;McCown, 2002;Woodward et al, 2008;Cerf et al, 2008). Besides, outside the strict domain of farming systems research, it has been shown, on the basis of a case study around a model to support upland water catchment management, that participatory modelling with people who interact with the systems in reality is relevant to gain a more integrated view of the modelled systems (Prell et al, 2007).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Another challenge is to build models that will easily be appropriable by farmers and that will allow them to consider in-depth changes. Building them in a participatory way with farmers could be one way of making them more appropriable (Newman et al, 2000;McCown, 2002;Woodward et al, 2008;Cerf et al, 2008). Besides, outside the strict domain of farming systems research, it has been shown, on the basis of a case study around a model to support upland water catchment management, that participatory modelling with people who interact with the systems in reality is relevant to gain a more integrated view of the modelled systems (Prell et al, 2007).…”
Section: Resultsmentioning
confidence: 99%
“…Lastly, the place given to the targeted users in the design process of the model can vary among models, from no actors' involvement to a participation that dictates the very structure of the model. Moreover, there is an increasing concern in the agricultural sciences about the users' participation, which can make the models more appropriable (Newman et al, 2000;McCown, 2002; Cerf et al, 2008;Woodward et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Secondly, viewing sustainability as a process implies a cyclic epistemological model (in contrast to the linear knowledge model discussed above), which evolves through time, as do the needs and sustainability goals of individuals (see also the 'adaptation cycle' described by Meinke et al 2009). Research that straddles the generation of new knowledge and the various perceptions of what constitutes reliable and relevant knowledge in the face of complex and changing political, economic, social and bio-physical environments has been described as ''boundary work'' (Guston 2001;Clark et al 2011) or ''participatory action research'' McCown 2001McCown , 2002. Boundary work using bio-physical modelling has been applied successfully in Australia, where it involved iterative learning cycles in which the participating researchers, policy-makers and farmers (re-)designed and (re-)evaluated simulation scenarios as informed by practical experience and empirical observations (Meinke et al 2001;Kokic et al 2007;Nelson et al 2007Nelson et al , 2010a.…”
Section: Discussionmentioning
confidence: 99%
“…Farm management research is focused more on describing farmers' decision-making processes and decision outcomes than on information management issues, which are generally dealt with indirectly through the analysis of farmers' decision-making processes: 'information is an input required in every step of the decision-making process, that is, goal formulation, problem recognition, problem formulation (identifying the causes of problems), preselection of alternative actions, and in more general terms, in uncertainty reduction' (Timko and Loynes, 1989;Solano et al, 2003). According to McCown (2002), decision support systems (DSSs) are information systems (ISs), and like them 'were designed to serve functions deemed by ''management scientists'' to be potentially useful to managers'. However, the fact that farmers have been slow to adopt DSS models and DSS outputs raises the question of how these 'management scientists' have modelled farm-targeted information and information management.…”
Section: Introductionmentioning
confidence: 99%